PENERAPAN EVALUASI DALAM PENDIDIKAN ISLAM (STUDI KASUS PONDOK PESANTREN SALAFIYAH DARUSSANA KINTAP) - Sugiharto, Muhammad Samuel; Huda, Nuril; Hermina, Dina (STIT Ibnu Rusyd Tanah Grogot, 2025)
The evaluation in Islamic education at Islamic boarding schools (pondok pesantren) plays a crucial role in assessing the progress of students (santri), both in academic aspects and character development. Through comprehensive evaluation, pondok pesantren can produce students who are knowledgeable, possess good morals, and are ready to contribute to society. This research aims to explore in depth the application of learning evaluation for students in Pondok Pesantren. This is a descriptive study with a qualitative approach conducted at an Islamic educational institution, namely Pondok Pesantren Darussana Kintap. The data collection techniques include observation, interviews, and document studies, which are then analyzed to determine the planning, implementation, evaluation, and outcomes of Islamic learning at Pondok Pesantren Darussana. The research results show that the systematic application of evaluation is able to shape and improve the quality of both academic learning and the morals of male and female students.